Luteinizing hormone-releasing hormone neurons express Fos protein during the proestrous surge of luteinizing hormone. - Lee, W S (1990)
The ability of luteinizing hormone-releasing hormone (LHRH) neurons to express the oncogene c-fos was examined during the estrous cycle in rats. The immunocytochemical localization of the c-fos-encoded antigen, Fos, was coupled with the immunocytochemical localization of LHRH. LHRH neurons showed no Fos immunoreactivity during diestrus-1, diestrus-2, estrus, or the morning of proestrus. However, Fos was expressed in LHRH neurons from 1600 to 2200 hours during proestrus. The timing of onset of Fos expression in LHRH neurons during proestrus suggests a strong correlation with increased LH secretion. Pentobarbital, which blocks the preovulatory LH surge, blocked Fos expression in LHRH neurons, but the LHRH neurons expressed Fos on the following afternoon at the time of the expected delayed LH surge. Not all LHRH neurons expressed Fos during the LHRH surge. Approximately half of the LHRH neurons were activated in the preoptic area and anterior hypothalamus; more anteriorly positioned LHRH neurons did not express Fos, resulting in an overall stimulation of 40% of the LHRH neurons. These data provide direct evidence that stimulation of LHRH neurons during proestrus takes place at the LHRH cell bodies, and identify the specific population of LHRH neurons which are activated.